Immune Cell Engagers: Advancing Precision Immunotherapy for Cancer Treatment - Hyukmin In; Minkyoung Park; Hyeonsik Lee; Kyung Ho Han (Antibodies)
Immune cell engagers (ICEs) are an emerging class of immunotherapies designed to harness the immune system’s anti-tumor potential through precise targeting and activation of immune effector cells. By engaging T cells, natural killer (NK) cells, and phagocytes, ICEs overcome challenges such as immune evasion and MHC downregulation, addressing critical barriers in cancer treatment. T-cell engagers (TCEs), led by bispecific T-cell engagers (BiTEs), dominate the field, with innovations such as half-life-extended BiTEs, trispecific antibodies, and checkpoint inhibitory T-cell engagers driving their application in hematologic and solid malignancies. NK cell engagers (NKCEs) and phagocyte cell engagers (PCEs) are rapidly progressing, drawing on NK cells’ innate cytotoxicity and macrophages’ phagocytic abilities to target tumors, particularly in immunosuppressive microenvironments. Since the FDA approval of Blinatumomab in 2014, ICEs have transformed the oncology landscape, with nine FDA-approved products and numerous candidates in clinical trials. Despite challenges such as toxicity, resistance, and limited efficacy in solid tumors, ongoing research into advanced platforms and combination therapies highlights the growing potential of ICEs to provide personalized, scalable, and effective cancer treatments. This review investigates the mechanisms, platforms, research trends, and clinical progress of ICEs, emphasizing their pivotal role in advancing precision immunotherapy and their promise as a cornerstone of next-generation cancer therapies.